Luminescent self-assembly formation on a gold surface observed by reversible 'off-on' switching of Eu(III) emission - GUNNLAUGSSON, THORFINNUR (My University, 2009)
The formation of a self-assembly between a sensitising antenna and an Eu(III) functionalised cyclen complex 1.Eu, tethered to a gold surface via a C(12) alkyl thiol spacer, is described where changes in the Eu(III) emission signal the formation, and dissociation, of a ternary complex.
PUBLISHED
Keywords: Chemistry